The effectiveness of the Ambu® AuraGain™ laryngeal mask on hemodynamic and respiratory parameters in patients undergoing septoplasty: A randomized prospective clinical study - Öterkuş, Mesut; Kuşderci, Hatice (Journal of Surgery and Medicine, 2021)
Background/Aim: The use of laryngeal masks is increasing with the introduction of 3rd generation airway vehicles. However, endotracheal intubation is preferred by most anesthesiologists in septoplasty operations due to airway safety concerns. In this study, we aimed to compare the 3rd generation airway device, Ambu® Auragain ™ LMA, with tracheal intubation in terms of hemodynamic and respiratory parameters. Methods: This study included 69 patients aged 18–60 years with an ASA score of 1–2 who were scheduled for septoplasty in Adıyaman University Research and Educational Hospital between 2016.01.01 and 2017.06.31. Study groups were randomly defined as Group 1 - Ambu® AuraGain™ laryngeal mask (LMA, n = 37) and Group 2 - endotracheal intubation (ETT, n = 32), and the hemodynamic and respiratory parameters were measured and recorded. Results: The demographic data and partial oxygen saturation of the patients were similar (P>0.05 for all values). The patients in the ETT group had a higher heart rate at induction, intubation and at the first minute compared to the LMA group (P<0.05 for all values). The mean arterial pressure was significantly lower at induction, intubation, at minutes 1, 2, 3, and 4 of intubation, and at extubation in the LMA group (P<0.05 for all values). Conclusion: The Ambu® AuraGain™ laryngeal mask was similar to or better than tracheal intubation in terms of hemodynamic and respiratory parameters. The Ambu® AuraGain™ LMA can be used as an equivalent to tracheal intubation in terms of hemodynamic and respiratory parameters.